Competitiveness of African agricultural value chains - DEDEHOUANOU, SENAKPON FIDÈLE ANGE; Dimaranan, Betina; Laborde, David (My University, 2019)
The second annual Africa Agriculture Trade Monitor assesses emerging and long-term trends and drivers shaping Africa’s trade in agricultural products and evaluates the possible impacts of current trade tensions. The 2019 report focuses on intraregional trade and competitiveness, with chapters on measuring regional trade integration and competitiveness of agriculture, a feature chapter on the potential impact of global trade tensions, and an in-depth look at trade integration in the Eastern and Southern Africa region.
Keywords: trade; exports; imports; agricultural trade; production possibilities